Filler–filler and rubber–filler interactions in nitrile rubber/silica composites. Issue 1 (February 2014) - Kapgate, Bharat P.; Das, Chayan
Abstract : The effects of surface modification on the filler–filler and rubber–filler interactions in silica-filled nitrile rubber composites have been studied. Nitrile rubber composites are prepared with untreated stöber silica, organosilane-treated stöber silica and externally added precipitated silica along with organosilane. Morphological studies show better filler dispersion in composites containing silane-treated Stöber silica–filled composites. The studies of the mechanical properties and dynamic mechanical analysis reveal the strong filler–filler interaction (silica agglomerates) in untreated Stöber silica–filled and externally added precipitated silica-filled composites. On the other hand, better rubber–filler interaction is observed for composite filled with Stöber silica treated with bifunctional organosilane.